FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN DI KEPULAUAN NUSA TENGGARA - Putra, I Putu Nata Mahesa; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 8 (2020): VOL 9 NO 8, AGUSTUS 2020 (1631 - 1887), 2020)
Poverty is a problem that has become a matter for all countries be overcome with a variety of solutions. The poverty between provinces in Nusa Tenggara Islands in 2019 shows  considerable distance. This study to analyze factors influence economic growth and poverty rates in the Nusa Tenggara islands. Analysis technique used path analysis. The results of this study are Regional Minimum Wages, Education Level, and Health Level have a positive significant effect on economic growth. Regional minimum wages, education levels, health levels, and economic growth have a negative significant direct effect on poverty levels in the Nusa Tenggara archipelago. Education level has an indirect effect on poverty levels through economic growth so that economic growth is an intervening variable. Regional minimum wages and health levels do not have an indirect effect on poverty levels through economic growth, as indicated by economic growth, not as a mediating variable. Keywords: economic growth, poverty level, UMR, education level, health level